END TB – THE NEW WHO STRATEGY IN THE SDG ERA* , AND THE CONTRIBUTIONS FROM THE RUSSIAN FEDERATION - M. C. Raviglione; A. A. Korobitsyn (Туберкулез и болезни лёгких)
This article is written to update tuberculosis (TB) experts in the Russian Federation about the most recent data on the global TB situation, the progress in global TB care and control efforts, the challenges ahead, and the response expected by all countries. In particular, the article will detail the new End TB Strategy that the World Health Organization (WHO) is promoting for the new era of the Sustainable Development Goals 2016-2030 after the World Health Assembly approved it in a resolution during its 2014 meeting. The Russian Federation, with its extraordinary resources and knowledge needs to contribute to the roll-out of the new Strategy, both nationally and internationally. For this, the Ministerial Conference called by the Russian Federation Government to be held in Moscow on 16-17 November 2017 will play a crucial role in calling for the political attention necessary at the highest governmental levels in all high-burden countries, with an ultimate aim to raise the struggle against TB in the heads-of-state agenda.